Makna Siloka (Filosofis) Lirik Lagu Goyang Karawang Karya Lingga Angling Raspati - Yousef Bani Ahmad; Siti Gomo Attas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Singaperbangsa Karawang, 2022)
Karawang is one of the districts in West Java. The city of Karawang is known as a rice barn, a city of heroes, and an industrial city. In the field of art, Song Goyang Karawang is one of the works of young people who become local cultural identities and still maintain their identity in facing the challenges of foreign cultures that enter Indonesia. Goyang karawang song is a product of historical art culture. The aims of this study are 1) to understand the denotative meaning that appears in the lyrics of the song rocking karawang by Lingga Angling Raspati, 2) what the connotation meaning of the lyrics of the song Goyang Karawang is like. The researcher used a qualitative approach and content analysis methods. Sources of data were taken from literature studies and interviews with songwriters, namely Angga Angling Raspati. From the results of the study, it was found that the song has the meaning of changing the rocking karawang paradigm which was different from today. Goyang karawang means Karawang continues to move to grow, progress and develop. The cultural meaning found in the lyrics is a depiction of the life of the people of the city of Karawang which has a lot of rice fields and also industries. In industry, people generally work in companies and it is proven by the existence of Karawang International Industrial City (KIIC). The impact of the meaning of the song is to convey a true meaning of rocking karawang itself.